2021
DOI: 10.21037/cco-20-230
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gallbladder cancer in the Unites States: a population-based study

Abstract: Background: Gallbladder cancer (GBC) is the most common neoplasm of the biliary tract with the lowest rates of survival. Most GBCs are adenocarcinomas that arise from the epithelial lining of the gallbladder. There are limited data in the literature regarding the epidemiology of GBC. Using a large database, we aim to describe the epidemiology using a US population database. Methods: A multi-institutional database (Explorys Inc., Cleveland, OH, USA) was surveyed. A cohort of patients with a primary malignant ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…These results consisted of a recently published study and previous studies. 2,[20][21][22][23] and cancer risk, and the results also suggested a 21-fold and 42-fold increased risk of hepatobiliary cancers in patients with AIH and PBC respectively. 20 In addition, sensitivity analyses suggested that the results were stable (AIH: RR = 12, PBC: RR = 14).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These results consisted of a recently published study and previous studies. 2,[20][21][22][23] and cancer risk, and the results also suggested a 21-fold and 42-fold increased risk of hepatobiliary cancers in patients with AIH and PBC respectively. 20 In addition, sensitivity analyses suggested that the results were stable (AIH: RR = 12, PBC: RR = 14).…”
Section: Discussionmentioning
confidence: 73%
“…In this study, patients with AiLD were mainly reported to be associated with hepatobiliary cancers, and we found a 22‐fold higher risk of hepatobiliary cancers in these patients (AIH: RR = 12, PBC: RR = 16, PSC: RR = 139). These results consisted of a recently published study and previous studies 2,20–23 . It is noteworthy that the recent study published in JAMA Oncology investigated the relationship between immune‐mediated diseases (including AIH and PBC) and cancer risk, and the results also suggested a 21‐fold and 42‐fold increased risk of hepatobiliary cancers in patients with AIH and PBC respectively 20 .…”
Section: Discussionmentioning
confidence: 96%
“…Globally, GBC is a rare, but aggressive malignancy of the biliary tract. [1][2][3][4][5] Epidemiological studies reported that its incidence and prevalence increase annually. [30][31][32] Thus, the management of this fatal disease is urgent.…”
Section: Discussionmentioning
confidence: 99%
“…Gallbladder cancer (GBC) is the most common distinct subset of biliary tract cancer worldwide. [1][2][3] It is a rare but highly lethal malignant disease with a worldwide incidence of 2 per 100,000 persons. [4][5][6][7] In addition, its incidence is relatively high, with a significant geographic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Gallbladder cancer (GBC) is the most common biliary malignancy and the sixth most common gastrointestinal malignancy, with a prevalence rate ranging from 8.5 cases per 100,000 population in the United States (US) to 13.6 cases per 100,000 in Asian populations [ 1 ]. GBC occurs relatively often in certain geographic locations, such as Chile, North India, South Korea, Japan, and New Mexico (US) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%